Expression of the Homeobox GenesOTX2andOTX1in the Early Developing Human Brain - Karen Bonde Larsen; Melissa C. Lutterodt; Kjeld Møllgård; Morten Møller (2010)
In rodents, the Otx2 gene is expressed in the diencephalon, mesencephalon, and cerebellum and is crucial for the development of these brain regions. Together with Otx1, Otx2 is known to cooperate with other genes to develop the caudal forebrain and, further, Otx1 is also involved in differentiation of young neurons of the deeper cortical layers. We have studied the spatial and temporal expression of the two homeobox genes OTX2 and OTX1 in human fetal brains from 7 to 14 weeks postconception by in situ hybridization and immunohistochemistry. OTX2 was expressed in the diencephalon, mesencephalon, and choroid plexus, with a minor expression in the basal telencephalon. The expression of OTX2 in the hippocampal anlage was strong, with no expression in the adjacent neocortex. Contrarily, the OTX1 expression was predominantly located in the proliferative zones of the neocortex. At later stages, the OTX2 protein was found in the subcommissural organ, pineal gland, and cerebellum. The early expression of OTX2 and OTX1 in proliferative cell layers of the human fetal brain supports the concept that these homeobox genes are important in neuronal cell development and differentiation: OTX1 primarily in the neocortex, and OTX2 in the archicortex, diencephalon, rostral brain stem, and cerebellum.